FORMATION OF STUDENTS' CREATIVE THINKING THROUGH ART-PEDAGOGICAL TECHNOLOGIES - Ilyasova Umida Azizovna (Modern American Journals, 2025)
This article examines the application of art-pedagogical technologies in the educational process and the possibilities of developing students' creative thinking as a result. The study analyzes the role of art therapy, musical education, theater element, fine arts and other art-based approaches in the formation of students' independent thinking, imagination, and problem-solving skills.
Keywords: Art pedagogy, creative thinking, art, educational technology, students, creativity